PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN - Novita Sari; Bunga Putri Praselia (JURNAL FAIRNESS, 2023)
Financial performance is a measure of the extent to which an entity or company achieves its financial and operational goals. Operational activities in a banking can be seen from the financial conditions in a period, both in terms of collecting funds and distributing funds. This research aims to determine the effect of managerial ownership, institutional ownership, and audit committee on financial performance using banking companies from 2016-2022. This research uses secondary data. The sample used in this research was 36 companies with 252 observations. The results of this research indicate that the managerial ownership variable has a positive effect on financial performance. Meanwhile, institutional ownership and audit committee have no effect on financial performance. The implications of this research for investors and future researchers are that it can be used as material for consideration by management, shareholders, investors and other interested parties in making investment decisions and policies, so that it can produce optimal investment and it is hoped that the results of this research can become a reference. in subsequent research with similar research. Based on the results of this research, it is recommended that future researchers can increase the research sample by increasing the number of samples by increasing the number of companies or increasing the number of years of observation.